DEVELOPMENT OF TEXTBOOK FOR GRAMMATICAL MATERIAL BASED ON SCIENTIFIC APPROACH TO IMPROVE WRITING SKILLS | تطوير الكتاب التعليمي في مادة التراكيب على أساس المدخل العلمي لترقية مهارة الكتابة - Rizka Utami (Abjadia, 2020)
Teaching and learning process can not be separated from textbooks that play an important role as a reference for teachers and students. A good textbook must be representative of the curriculum that applies both the material and teaching methods so that learning objectives are achieved. Arabic textbooks in the 2013 curriculum use a scientific approach, but grammar material has not been explained in detail so that it affects students' competence to improve language skills. So the researcher developed a book for grammar material based on a scientific approach to improve writing skills. This study aims to develop books based on a scientific approach and determine the effectiveness of the books developed. The results obtained from this study are that the books developed have scored between 80-100% which means very good and can be used in learning without any improvement. While the effectiveness aspect obtained a significance value of around 10.93 which shows that the textbook for grammatical material based on scientific approach is effective to improving students’ writing skills.